The Importance of Listening and Understanding in Basic Foreign Language in Higher Education Institutions - Makhsudakhon Abbasovna, Saidova (International Journal of Psychosocial Rehabilitation, 2020)
Living and studying - in remote rural areas, it is not always possible to go to big cities and enter university. The technology of listening and understanding of distance learning comes from their city and allows you to read without leaving. Teaching and Accompanying - Students have the opportunity to study without leaving work, which is especially helpful for undergraduates or second-year students.